Evolving impact of the COVID-19 pandemic in chronic dialysis recipients in France - Elhadji Leye; Khalil El Karoui; Tristan Delory; Maude Espagnacq; Myriam Khlat; Sophie Le Coeur; Nathanaёl Lapidus; Gilles Hejblum; On behalf of the COVID-HOSP working group (Communications Medicine)
Abstract Background This observational study aimed to assess the impact of the pandemic on the way kidney transplantation, survival, and vaccination evolved in chronic dialysis recipients (CDR) over the course of the COVID-19 pandemic waves and inter-waves. Methods Using the French national health claims database, incident persons with end-stage kidney disease in the years 2015 to 2021 treated with dialysis were followed up until 31 December, 2022. Kidney transplantation and survival in the pandemic sub-periods compared to the pre-pandemic period were investigated using longitudinal models with time-dependent covariates. In addition, the impact of cumulative doses of COVID-19 vaccine on hospitalization and survival was studied, comparing CDR and matched controls. Results Here, we show that the follow-ups of the 71,583 CDR and the 143,166 controls totalize 639,341 person-years (CDR: 184,909; controls: 454,432). The likelihood of receiving a kidney transplant is lower in all pandemic sub-periods. The 3 waves are associated with a higher risk of death (hazard ratio (HR [95% confidence interval]): 1.19 [1.13–1.27], 1.19 [1.15–1.23], and 1.12 [1.07–1.17], respectively). While vaccine coverage declines with each booster dose, receiving these doses is associated with a lower risk of COVID-19-related hospitalization (0.66 [0.56–0.77], 0.83 [0.72–0.94] for 1st booster versus 2nd dose and 2nd booster versus 1st booster, respectively) and death (corresponding HR: 0.55 [0.51–0.59], 0.88 [0.83–0.95]). Conclusions The evolving patterns in mortality and vaccination outcomes are similar in CDR and controls, suggesting that the impact of the pandemic on CDR is not specific to kidney disease per se.